Analisis Kualitas Pelayanan Calon Tenaga Kerja Indonesia di Dinas Sosial Tenaga Kerja dan Transmigrasi Kabupaten Pati - Saputra, Ardian Hadi; Mustam, Mochammad; Yuniningsih, Tri (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Indonesia's Labor candidate or candidates are often referred to by the term TKI for Indonesia's citizens are going to work abroad in a working relationship for a period of time with pay. The main purpose of this research is to analyze the quality of service of candidates as well as provide a solution in the TKI improved service quality in the service of Social prospective TKI manpower and transmigration Pati. Standar services already contained in the prospective TKI Act No. 39 of 2004 which contains about the placement and protection of Indonesia Labor abroad.Service quality prospective migrant workers in social dept. manpower and transmigration district starch seen in theory zeithman dkk ( 1990 ) consisting of 5 dimensions namely dimensions tangible, reliability, dimensions dimensions responsivines, dimensions assurance and empathy dimension.Show that service quality prospective migrant workers in social dept. manpower and transmigration district starch is enough quality. Besides also contained a correlation coefficient a positive relationship and significant between dimensions 5 dimensions service quality and satisfaction service.Based on the level of interest in improving the quality of indonesian candidate service ( there are 3 ) pioritas three main candidates in improving the quality of service in aspect of indonesian namely. service, speed comfort and ease service place in the process of services. That writer recommended on aspects speed service by means of increasing employment and need held diklat, to comfort service place by means of adding facilities as air conditioning / ac tv and fix the seat. At ease in the process of service by means of service, installed boards alur make a queue electronic system adding machine fotocopy.